1980
DOI: 10.1073/pnas.77.1.577
|View full text |Cite
|
Sign up to set email alerts
|

[Phe4]somatostatin: a potent, selective inhibitor of growth hormone release.

Abstract: [Phe4]Somatostatin was twice as active as somatostatin (SS) in suppressing rat growth hormone release in vitro but had only weak activity toward inhibition of insulin and glucagon release in vivo. The ability of this analogue to inhibit growth hormone release more actively than SS was confirmed in vivo by two separately designed bioassays. Further structure/activity studies of position 4 were carried out with [Glu4]SS, [Thr4]SS, and des-Lys4-SS, all of which had negligible inhibiting activity in the pituitary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

1983
1983
2009
2009

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…Better evidence for dissociation between pituitary and cortex SRIF recep tors is obtained by competition with several synthetic SRIF analogs. Substitution of D-5-F-Trp and D-5-Br-Trp for the Trp8 residue results in potent pituitary SRIF agonists [18]. However, only the fluorinated analog exhibits such en hanced competition (32 times more potent than SRIF) for SRIF binding to cortex membranes [35].…”
mentioning
confidence: 99%
“…Better evidence for dissociation between pituitary and cortex SRIF recep tors is obtained by competition with several synthetic SRIF analogs. Substitution of D-5-F-Trp and D-5-Br-Trp for the Trp8 residue results in potent pituitary SRIF agonists [18]. However, only the fluorinated analog exhibits such en hanced competition (32 times more potent than SRIF) for SRIF binding to cortex membranes [35].…”
mentioning
confidence: 99%
“…Murphy, Redding, Arimura and Schally 1980) and [D-5Br-Trp 8 , D-Cys 14 ]-SRIF {Hirst, Show, Meyers and Coy 1980) were reported to be specific for GH suppression.…”
Section: Discussionmentioning
confidence: 94%
“…Murphy et al (30,31) have shown that alteration of Lys4 results in analogs with selective inhibition of growth hormone release. The importance of Lys4 seems to be shared by both intestinal ion transport properties and inhibition of the release of growth hormones.…”
Section: Discussionmentioning
confidence: 99%